Case of epithelioid hemangioendothelioma occurring in the postradiation setting for breast cancer. Issue 2 (10th November 2020) - Hahn, Elan; Dickson, Brendan C.; Gupta, Abha A.; Nofech‐Mozes, Sharon
Abstract: Epithelioid hemangioendothelioma (EHE) is a rare malignant vascular tumor, which is typically characterized by recurrent fusion genes. EHEs most commonly occur in the lung, liver, bone, and internal organs. EHE has rarely been reported to occur in the post‐radiotherapeutic setting, the breast site or in association with breast cancer. The differential diagnosis for radiation‐associated vascular lesions of the breast is classically limited to atypical vascular lesion and angiosarcoma and does not include EHE. We present the case of a woman with a history of breast cancer and post‐surgical radiotherapy who went on to develop an EHE of the chest wall skin within 3 years of the completion of radiotherapy. Microscopically, the lesion was infiltrative and composed of anastomosing nests of epithelioid‐to‐spindled cells with eosinophilic and vacuolated cytoplasm. By immunohistochemistry, the cells were positive for ERG, D2‐40, and CD31. The diagnosis was confirmed by identification of a characteristic WWTR1 ‐ CAMTA1 fusion gene using RNA sequencing. This case expands our understanding of radiation‐associated tumors.